PROFESSIONAL DEVELOPMENT ACTIVITY AND TEACHERS’ LEARNINGEXPERIENCES IN THE MIDST OF THE COVID-19 PANDEMIC - Felicia Fitria Rahmadhina; Ani Pujiastuti White (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
This paper descriptively discusses the type of professional development activities attended by teachers during the Covid-19 pandemic and what learning and experience they obtained from the activities. The data are gathered qualitatively from open-ended questionnaires. The participants involved elementary school teachers from several regions in Indonesia. The participants (N=56) described various types of professional development activities they attended during the Covid-19 pandemic, which consisted of webinars, training, seminars, workshops, teachers gathering and networking, online courses, and supervision. The teachers also state that they obtained benefits from the professional development activities they attended. It is recommended that further researchers can study various aspects of professional development activities for teachers in Indonesia, especially in the contexts of elementary school and pre-service teachers.